2021
DOI: 10.3389/fcimb.2021.747739
|View full text |Cite
|
Sign up to set email alerts
|

EgGLUT1 Is Crucial for the Viability of Echinococcus granulosus sensu stricto Metacestode: A New Therapeutic Target?

Abstract: Cystic echinococcosis (CE) is a zoonotic parasitic disease caused by infection with the larvae of Echinococcus granulosus sensu lato (s.l.) cluster. It is urgent to identify novel drug targets and develop new drug candidates against CE. Glucose transporter 1 (GLUT1) is mainly responsible for the transmembrane transport of glucose to maintain its constant cellular availability and is a recent research hotspot as a drug target in various diseases. However, the role of GLUT1 in E. granulosus s.l. (EgGLUT1) was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…In experimentally infected mice, a 10 mg/kg dose of WZB117 exhibited significant reduction of number and size of hydatid cysts as efficiently as albendazole. In addition, no change was observed in either body weight or blood glucose level in the treated mice for 4 weeks [65] .…”
Section: Cytochrome C Complex (Cyt C)mentioning
confidence: 86%
See 1 more Smart Citation
“…In experimentally infected mice, a 10 mg/kg dose of WZB117 exhibited significant reduction of number and size of hydatid cysts as efficiently as albendazole. In addition, no change was observed in either body weight or blood glucose level in the treated mice for 4 weeks [65] .…”
Section: Cytochrome C Complex (Cyt C)mentioning
confidence: 86%
“…Transporters: Recently, Amahong et al [65] proposed glucose transporter 1 (GLUT1), responsible for the transmembrane transport of glucose, a promising drug target in E. granulosus. They cloned EgGLUT1 encoding gene from E. granulosus sensu stricto and observed its essentiality for glucose uptake and protoscoleces viability.…”
Section: Cytochrome C Complex (Cyt C)mentioning
confidence: 99%
“…ABZ and HM (both 120 μM) were used as positive controls, and the viability of PSCs was detected by a 1% eosin staining assay after 48 h of in vitro treatment (PSCs that turned red after eosin staining were considered dead while surviving PSCs were colorless). 19 Each experiment was repeated at least three times. PSCs were collected for observation by scanning electron microscopy (SEM) (LEO1430VP, LEO company, Germany) after drug intervention, and the experiments were performed as previously described.…”
Section: Methodsmentioning
confidence: 99%
“… 23 Randomly selected treated mouse cysts were observed by transmission electron microscopy (TEM) (JEM1230, JEOL company, Japan) as described previously. 19 …”
Section: Methodsmentioning
confidence: 99%
“…Surgery and anti-helminthic drugs are the treatment of choice for AE (3). Some proteins of E. multilocularis with high immunogenicity could induce immune responses to prevent infection (4)(5)(6)(7). Our previous study has shown that vaccination with dominant epitopes, such as EMY162, Glut1, TSP3, 14-3-3 and EM-LAP, could significantly decrease the number and size of cysts in a mouse model infected with E. Multilocularis metacestodes.…”
Section: Introductionmentioning
confidence: 99%